Four Programs to Improve Students' English Skills at Modern Islamic Boarding Schools - Oktavia, Neri; Munir, Sirajul; Demina, Demina; Hendriani, Suswati; Hidayat, Rahmat (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The main issue in this research is how the management of the English language skills improvement program for students at modern Islamic boarding school. The purpose of this study is to describe the program and its management in improving the language skills of the students at the institution. This research employs a qualitative approach, with data collected through interviews, observations, and documentation. The data sources are verified through primary and secondary data. The data processing is conducted descriptively and qualitatively, followed by classification of specific aspects of the problem and presented effectively. The findings from field research indicate that the English language skills enhancement program at modern Islamic boarding school consists of four main programs: i) intracurricular program, consists of grammar, dictation, English lesson, story for you, reading and speaking, ii) curricular program, consists of daily vocabularies, English conversations, English week, muhadharah, haflah al-Lughah, speech contest, iii) extracurricular program, consists of English club, debate club, and storytelling club, and iv) involves teacher training and teaching practice classes for santri. The planning carried out in this program aligns with the planning indicators, the organization is well-structured, the implementation follows the program accordingly, and the supervision complies with the established planning and standards.